Towards The Development Of Universal Islamic Leadership Model: Reviewing The Existing Islamic Leadership Theories And Models - Abdul Kadir Othman; Muhammad Iskandar Hamzah; Arifi Ridzuan (Journal of Islamic Management Studies, 2018)
Currently, there are several Islamic leadership models developed by various authors around the world which created perplexity rather than clarity among the academics and practitioners. Although the popular excerpt says “the differences in people bring benefits to others” is true, but in this academic endeavour, a common agreement on the definitions and the underlying dimensions of Islamic leadership styles are greatly required. Having so many theories and models of Islamic leadership make academics and researchers struggle to decide on the most appropriate model to pursue their novel investigation. Realizing the need to have a universal model of Islamic leadership, this paper discusses the existing leadership theories and models and proposes the one that can be regarded as the common model. It is expected that the proposed model might facilitate research on Islamic leadership and its nomological networks can be established.